2007
DOI: 10.1016/j.immuni.2007.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Notch Directly Regulates Gata3 Expression during T Helper 2 Cell Differentiation

Abstract: Notch signaling plays multiple roles to direct diverse decisions regarding cell fate during T cell development. During helper T (Th) cell differentiation, Notch is involved in generating optimal Th2 cell responses. Here, we present data investigating how Notch mediates Th2 cell differentiation. Notch showed a CD4(+) T cell intrinsic role in promoting IL-4 expression that required GATA-3. In the absence of Notch signals, Gata3 expression was markedly diminished. Introduction of an activated allele of Notch1 int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
307
2
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 326 publications
(330 citation statements)
references
References 52 publications
19
307
2
2
Order By: Relevance
“…However, distinct Notch receptors may have different effects on peripheral T cell responses. In two recent studies, Notch1 and Notch2 were shown to directly regulate GATA3 expression and to promote Th2-type polarization (29,30). In another study, CD4 ϩ T cells isolated from transgenic mice expressing a Notch1 antisense construct produced reduced amounts of IFN-␥ (15).…”
Section: Discussionmentioning
confidence: 99%
“…However, distinct Notch receptors may have different effects on peripheral T cell responses. In two recent studies, Notch1 and Notch2 were shown to directly regulate GATA3 expression and to promote Th2-type polarization (29,30). In another study, CD4 ϩ T cells isolated from transgenic mice expressing a Notch1 antisense construct produced reduced amounts of IFN-␥ (15).…”
Section: Discussionmentioning
confidence: 99%
“…CD25 (IL2-R and preTa, pre-T-cell receptor alphachain) were also shown to be Notch target genes in T-cells [19,20]. In later stages of T-cell development, the transcription factor GATA3, a master regulator for Tcell development and later for Th1/2 lineage decision, is a direct Notch target gene [21,22]. Flavell and colleagues could show that Th2-mediated immunity depends on either RBP-J or Notch [22] and that the GATA3 promoter contains bona fide RBP-J binding sites.…”
Section: Notch Target Genesmentioning
confidence: 99%
“…Flavell and colleagues could show that Th2-mediated immunity depends on either RBP-J or Notch [22] and that the GATA3 promoter contains bona fide RBP-J binding sites. In addition, the Pear lab demonstrated, that the expression of dominant-negative mastermindlike-1 (dnMAML) results in impaired GATA3 transcription levels and subsequently impaired IL4 production [21]. Two other Notch target genes, NRARP and Deltex-1 were shown to be potent negative regulators of Notch signaling [23,24].…”
Section: Notch Target Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…Later studies showed that Notch was also involved in mammalian differentiation processes including those governing the development of the immune system (19). The latter included evidence for a role of Notch signaling in the intrathymic differentiation of T cells (20 -22) as well as Th cell development in the periphery (23)(24)(25)(26)(27). Notch is, like TGF-␤, an evolutionarily conserved molecule but, unlike TGF-␤, is a type I transmembrane receptor rather than a receptor ligand.…”
mentioning
confidence: 99%